The development of multimedia courseware on UNIMAS online learning system - Wong, Sheng Tung (Universiti Malaysia Sarawak, UNIMAS, 2009)
This project aims to develop a multimedia courseware for academic staff of Universiti Malaysia Sarawak (UNIMAS), particularly the lecturers, to obtain basic knowledge and skill on how to use Morpheus, the UNIMAS online learning system. The objectives of the project are to create relevant text, images, flash files, and videos and integrate them into a functional multimedia courseware. In the process of developing this courseware, three software programmes, Macromedia Flash 8, Adobe Captivate 3, and Adobe Photoshop 7, were used. Besides, the model for design and development by Alessi and Trollip (2001) was also used to guide for the development process of this courseware. This model explains the various stages in creating the courseware. After the alpha system was created, it was evaluated by a subject matter expert. Then, it was revised and a beta system was created. After that, the beta system was evaluated by three potential learners. Then, the system was revised again. Finally, a functional final product was developed.